On Antiproton Production in 158 GeV/c Proton-Carbon Collisions and Nuclear Temperature of Interacting System - Fu-Hu Liu; Ya-Hui Chen; Ya-Qin Gao; Hua-Rong Wei (Advances in High Energy Physics)
The multisource thermal model is used in this paper to analyze the antiproton (p¯) production process in high-energy proton-carbon (p-C) collisions. The transverse momentum, Feynman variable, and rapidity distributions of antiprotons in the nucleon-nucleon center-of-mass system are calculated by using the model. The modeling results are compared and found to be in agreement with the experimental data measured by the NA49 Collaboration at 158 GeV/c beam momentum. As a parameter, the nuclear temperature of interacting system extracted from the antiproton spectrum is estimated to be about 150 MeV.